Etika Peserta Didik Terhadap Guru (Studi Analisis Terhadap Kitab Akhlak Lil Banin Karya Syeikh Umar Bin Ahmad Baradja) - Aang Andi Kuswandi; Imas Masitoh (AUD Cendekia, 2021)
This study aims to analyze the ethics of students towards teachers in the book Akhlak lil banin by Sheikh Umar bin Ahmad Baradja. This study uses a qualitative research method with a library research approach. Sources of data in this study are divided into two, namely primary library sources and secondary library sources. The primary library source in this research is the book of Akhlak Lil Banin by Syekih Umar bin Ahmad Baradja in volume I, while the secondary sources are his other works, books and journal articles that are relevant to the research topic. Data analysis uses content analysis techniques, namely collecting content related to the topic of the book of Akhlak Lil Banin for later analysis and drawing conclusions. The results of the study explain that students' ethics towards teachers according to him are sitting politely in front of the teacher, speaking politely, not interrupting the teacher's conversation, listening to what the teacher says, if you don't understand then ask gently and respectfully, always attend school every time. day, not skipping class and oversleeping for no good reason, hurry to class before the teacher enters class, obey the teacher's advice. All of these ethics are indeed simple, but according to him they.